Teachers’ social representations of inclusive education: A systematic review of literature 2010-2020 - María Francisca Muñoz-Oyarce; Manuel Monzalve-Macaya; Sergio Sepúlveda-Vallejos (Institute of Advanced Engineering and Science, 2023)
The inclusive education approach refers to the promotion of educability, welcoming all students in the same space. In this context, the systematic review aims to analyze the social representations of teachers about inclusive education in the preschool and elementary classroom, between the years 2010-2020. The study was conducted through a search in the Web of Science (WoS), Scopus, and EBSCO databases. Inclusion criteria such as language, empirical studies, last 10 years, and exclusion criteria considering duplicate articles and gray literature were applied. In the first iteration, a total of 86 original articles were obtained and after applying the exclusion and inclusion criteria, a total sample of 18 articles met inclusion criteria. An exhaustive content analysis of the selected research was carried out through a thematic analysis. The studies were organized in chronological order for descriptive and interpretative analysis. Among the most relevant findings of the study, the categories of diversity in the classroom; teachers and inclusive school; teaching-learning and inclusion stand out. The findings make it possible to respond to the objective of the study, highlighting the change in the teachers’ representations that allow a better understanding, valuation, and respect for the rights of all students, especially in early childhood. As for the conclusion, the adequate articulation between teachers’ representations and practices are essential aspects to generate a social transformation and guarantee an inclusive classroom in contexts of high social and cultural diversity.